Antibiotic treatment and long term prognosis of reactive arthritis. Issue 7 (1st July 2003) - Laasila, K; Laasonen, L; Leirisalo-Repo, M
Abstract : Objective: To evaluate whether a three month course of lymecycline has an effect on the long term prognosis of reactive arthritis (ReA). Methods: In 1987–88 a double-blind controlled study with three month course of lymecycline/placebo was conducted. 17 of 23 patients treated at the outpatient department of Helsinki University Central Hospital volunteered to take part in a follow up study, where a physical examination were performed, and erythrocyte sedimentation rate, C reactive protein, rheumatoid factor, and radiographs of the lumbosacral spine and sacroiliac joints and of symptomatic peripheral joints were examined. Results: 16/17 (94%) patients reported some kind of back pain and 10/17 (59%) peripheral joint symptoms during the follow up. Two patients had unilateral grade 1 sacroiliitis, one patient grade 4 sacroiliitis, and one patient bilateral grade 2 sacroiliitis. In one patient the disease had progressed to ankylosing spondylitis (AS), and in another to chronic spondyloarthropathy. In addition, two patients had small erosions in radiocarpal joints. No statistically significant differences were found between placebo and lymecycline groups in the development of chronic arthritis, sacroiliitis, or AS. Conclusion: The results of the initial study showed that long term treatment with lymecycline in patients with acute ReA decreased the duration of arthritis in those with Chlamydia trachomatis triggered ReA, but not in other patients with ReA. Ten years after the acute arthritis one patient had developed AS, and three had radiological sacroiliitis, three patients had radiological changes at peripheral joints. Long term lymecycline treatment did not change the natural history of the disease.